Counseling on Education to Prevent Anemia in Pregnant Women with Banana and Dragon Fruit: Penyuluhan tentang Edukasi Mencegah Anemia Ibu Hamil dengan Pisang dan Buah Naga - Munawar, Nabilah Herlim; Damayanti, Ruth; Yane Kumalaningrum; Putri Cahya Emilia; Primasari Oktaviani; Novelia, Shinta (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2025)
Anemia is one of the significant health problems in pregnant women. Anemia can cause death in pregnant women and is risky for both the mother and the fetus to be born. Anemia can be prevented from iron tablets and foods that contain high iron, as well as fruits such as Ambon bananas and red dragon fruit. This community service aims to overcome priority problems at the Cempaka Putih District Health Center, namely the high rate of low birth weight caused by anemia in pregnant women. This activity is focused on increasing the knowledge of pregnant women about preventing the risk of low birth weight caused by anemia and efforts to prevent anemia through the AKSI NGEMIL SANG NAGA program. The data that our group took was secondary data that we obtained from the Local Area Reporting (PWS) GIZIKIA at the Cempaka Putih Health Center. From these data, the results showed a high incidence of low birth weight caused by anemia in pregnant women. So, we determined this problem to be the main one in the Cempaka Putih area of this community stage. The method used in this community service is the lecture/counseling method, discussion, and demonstration, targeting pregnant women TM I-III. The results of this community service went smoothly with 15 pregnant women, one cadre, and 1 PKK Pokja IV participant. This activity began with a pretest on 15 pregnant women participants; an average pretest score of 62 points was obtained. This shows that mothers' knowledge about anemia is still lacking, so counseling was carried out on anemia in pregnant women, and demonstrations of anemia prevention efforts by consuming Ambon bananas and dragon fruit. Participants seemed enthusiastic about participating in this activity; six mothers actively asked questions. Evaluation of the activity was carried out by giving a posttest to participants. The average posttest result was 97 points. This shows an increase in good knowledge from pregnant women about anemia to prevent low birth weight. Based on the results of the activities that have been carried out, there has been an increase in pregnant women's knowledge about anemia as an effort to prevent low birth weight.